Positive motivation in kindergarten children (Journal of the College of Basic Education, 2025)
The current research aims to identify positive motivation in kindergarten children. The researcher prepared a positive motivation scale after reviewing previous theories and studies related to the subject of her research. The positive motivation scale included (35) paragraphs distributed over (7) mechanisms, and each mechanism included (5) paragraphs. She prepared the scale instructions and pictures for each paragraph according to the scientific instructions for preparing the scales. The researcher determined the scale score (zero-1) with two alternatives: (correct answer - wrong answer). The researcher verified the psychometric properties of the research tools represented by: validity and reliability. Validity was verified in two ways: (apparent validity, construct validity), and the reliability of the positive motivation scale was extracted by (retesting and Kuder-Richardson equation 20).